2021
DOI: 10.4103/ija.ija_69_21
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve stimulator guided erector spinae plane block for post-operative analgesia after total abdominal hysterectomies: A feasibility study

Abstract: Background and Aims: The pain following total abdominal hysterectomy (TAH), a very commonly performed gynaecological surgery, is usually taken care of by various opioids, non-opioids, regional and peripheral nerve blocks. Erector spinae plane block (ESPB) under ultrasound guidance is a relatively new approach for postoperative analgesia in thoracic and abdominal surgeries. Ultrasound availability and expertise to use it is a limitation at times. The primary aim of this study was to determine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Prasad and colleagues [ 16 ] in their clinical trial, Peripheral nerve stimulator-guided erector spinae plane block for post-operative analgesia after total abdominal hysterectomies, concluded that the ESPB is effective in improving pain in females undergoing total abdominal hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Prasad and colleagues [ 16 ] in their clinical trial, Peripheral nerve stimulator-guided erector spinae plane block for post-operative analgesia after total abdominal hysterectomies, concluded that the ESPB is effective in improving pain in females undergoing total abdominal hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Studies have shown that ESPB provides adequate postoperative analgesia for thoracotomy, modified radical mastectomy, multiple rib fractures, lumbar spine surgery, caesarean sections, total abdominal hysterectomies, extracorporeal shockwave lithotripsy, hemiarthroplasty, hernia repairs and laparoscopic procedures. [ 8 12 ]…”
Section: Discussionmentioning
confidence: 99%